Disruption of components of vascular endothelial growth factor angiogenic signalling system in metabolic syndrome - Jesmin, Subrina; Akter, Shamima; Rahman, Md. Mizanur; Islam, Md. Majedul; Islam, A. M. Shahidul; Sultana, Sayeeda N.; Mowa, Chishimba N.; Yamaguchi, Naoto; Okazaki, Osamu; Satoru, Kawano; Kimura, Sosuke; Hiroe, Michiaki; Mizutani, Taro; Moroi, Masao (Thrombosis and Haemostasis, 2013)
Metabolic syndrome (MetS) is associated with impaired angiogenesis, a process that is chiefly regulated by vascular endothelial growth factor (VEGF) upon binding to its specific receptors, VEGF-R1 and VEGF-R2. The purpose of the present study was to assess trends or patterns in plasma levels of VEGF and its soluble receptors in subjects with (MetS) or without (non-MetS) MetS; and further examine their association with clinical or metabolic parameters using a subpopu-lation of South Asian country. A total of 1,802 rural Bangladeshi women aged ≥15 years were studied using a population-based cross-sectional survey. Plasma levels of VEGF were found to be significantly increased (MetS vs. non-MetS: 483.9 vs. 386.9, p<0.001), whereas, the soluble forms of VEGF receptors, sVEGF-R1 and sVEGF-R2, were significantly decreased in subjects with Mets (sVEGF-R1, MetS vs. non-MetS: 512.5 vs. 631.3, p<0.001; sVEGF-R2, MetS vs. non-MetS: 9,302.8 vs. 9,787.4, p=0.004). After adjustment for age and all potential variables, multiple regression analysis revealed that plasma levels of VEGF had significant positive association with blood glucose (p = 0.019) and body mass index (p = 0.007). We also found that mean plasma levels of VEGF increased in direct proportion to levels of MetS components. The present study is the first ever to demonstrate a positive association between trends in levels of plasma VEGF and MetS using a large sample size from South Asia. The association between plasma VEGF and MetS needs further investigations in order to clearly decipher the clinical predictive value and accuracy of plasma VEGF in MetS.
Keywords: Metabolic syndrome; vascular endothelial growth factor; rural Bangladeshi women; South Asian